Proceedings of XXIIIrd International Symposium on Lattice Field Theory — PoS(LAT2005) 2005
DOI: 10.22323/1.020.0292
|View full text |Cite
|
Sign up to set email alerts
|

The glue-ball spectrum of pure percolation

Abstract: We present a high-precision numerical study of 3D random percolation viewed as a confining gauge theory. Using large correlation matrices among multiform Wilson loops we determine the low-lying masses in various spin channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…where we have kept terms proportional to powers of µ in an implicit form, and defined similar averages as in previous cases. We define 24 , and use the explicit values for ε o n,1 , ε o n,2 , and get…”
Section: Neumann Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…where we have kept terms proportional to powers of µ in an implicit form, and defined similar averages as in previous cases. We define 24 , and use the explicit values for ε o n,1 , ε o n,2 , and get…”
Section: Neumann Boundary Conditionsmentioning
confidence: 99%
“…The Laplacian operator (∂ 2 ) exactly cancels the denominator in the propagator (C.6), and in the case when σ = σ ′ this contribution is then proportional to ∞ m=−∞ m k , and thus identically vanishes as well, under our regularization (see (B.2)). For the Neumann case (C.8), the additional contribution m =0 m k also vanishes, except when k = 0, and then it equals 1, but the case of k = 0 never appears24 . This formal identity, ∂ 2 ≡ 0, holds also on the boundary.E.…”
mentioning
confidence: 98%
“…The string tension σ and the other physical observables have the expected scaling behaviour dictated by the universality class of three-dimensional percolation, therefore such a theory has a well-defined continuum limit [30]. Moreover it has a non-trivial glueball spectrum [31] and a second-order deconfining transition at finite temperature T c with a ratio T c / √ σ ≃ 1.5 which turns out to be universal, i.e. it does not depend on the kind of lattice utilised nor on the specific percolation process considered (bond or site percolation).…”
Section: The Modelmentioning
confidence: 99%
“…The gauge theory dual to Q = 1 Potts model, corresponding to random percolation, has been studied in detail in [9]. In particular it has been shown that, although the gauge group is trivial, it behaves like a full-fledged gauge theory with a confining vacuum (corresponding to the percolating phase), a string tension having a well-behaved continuum limit, a non trivial glueball spectrum [10] and a deconfinement transition at a well determined temperature. In this talk I describe some new features of this kind of gauge models in the range 0 < Q < 1.…”
Section: Pos(lattice 2007)304mentioning
confidence: 99%